Artificial intelligence-based comparison of the effects of duodenojejunostomy and sleeve gastrectomy on pancreatic morphology in Zucker diabetic fatty rats - Schäfer, Luisa; Mályi, Ambrus Gabor; Fink, Jodok; Seifert, Gabriel; Fink, Mira; Herrmann, Stephan; Pohlen, Uwe; Hügel, Bernhard; Bronsert, Peter; Marjanovic, Goran; Fichtner-Feigl, Stefan; Lässle, Claudia (Frontiers in Surgery, 2026)
ObjectiveThis study aims to compare the effects of sleeve gastrectomy (SG), duodenojejunostomy (DJOS), and their combination (DJOS + SG) on glucose regulation and pancreatic histomorphology and function in Zucker diabetic fatty (ZDF) rats, using artificial intelligence (AI)–assisted tissue analysis to assess morphological alterations.MethodsForty-five male ZDF rats were randomized into three surgical groups (SG, DJOS, DJOS + SG). Oral glucose tolerance tests (OGTT) and insulin levels were assessed at 1, 3 and 6 months post-surgery. Pancreatic tissue was analyzed histologically and immunohistochemically for β-cell mass, PCNA and PDX-1 expression. QuPath software enabled AI-based quantification of acinar, adipose, and fibrotic tissue.ResultsDJOS and DJOS + SG improved glucose tolerance and increased fasting insulin compared to SG. Both bypass groups demonstrated greater β-cell mass and clustering, elevated PCNA and PDX-1 expression, and more acinar tissue. SG was associated with reduced β-cell presence and increased pancreatic adiposity.ConclusionMalabsorptive (DJOS) or combination bariatric procedures (DJOS + SG) significantly enhance glycemic control in the rat model. These effects are accompanied by increased β-cell numbers and clustering, as well as enhanced β-cell proliferation and differentiation. Furthermore, acinar glandular tissue is increased, while pancreatic adiposity is reduced following bypass surgery.